Authorship, authorship order and author contribution: a literature review - Silva, Ana Paula Araújo Cabral da (2022)
Introduction: Literature review regarding author concepts, author contribution, authorship order and author position in the article byline. Objective: Identify patterns in the literature regarding the attribution of authorship, as well as the different roles of authors. Methodology: The methodological procedure involved a bibliographic review in the PubMed database, covering a period from 1895 to 2021. Results: It discusses guidelines for attribution of authorship, presenting the functions of the first author, main author and corresponding author, according to patterns identified in the literature. It reports the criteria established to regulate the correct and complete identification of authors in papers, according to the following documents: Recommendations for the Conduct, Reporting, Editing, and Publication of Scholarly work in Medical Journals, proposed by the International Committee of Medical Journal Editors (ICMJE ); CSE Recommendations for Group-Author Articles in Scientific Journals and Bibliometric Databases, published by the Council of Science Editors (CSE); and the Contributor Roles Taxonomy (CrediT) – proposed by the Consortia Advancing Standards in Research Administration (CASRAI) and the National Information Standards Organization (NISO). Conclusion: Among the final considerations, it suggests the wide discussion of such documents among the Brazilian scientific community and their adoption by national journals